KONSEP RIBA DALAM PERSPEKTIF FIQIH MUAMALAH SERTA IMPLIKASINYA TERHADAP TANTANGAN EKONOMI MODERN - Marwin Lubisa; Muhammad Saidi; Fatmah Taufik Hidayat (PT. Hasba Edukasi Mandiri, 2026)
Riba is a fundamental concept in Islamic commercial jurisprudence (fiqh muamalah) that is explicitly prohibited in Islamic teachings due to its association with injustice, exploitation, and economic inequality. This article aims to analyze the concept of riba from the perspective of classical Islamic jurisprudence and to examine its relevance in addressing the challenges of the modern economy, which is characterized by the complexity of global financial systems, conventional banking practices, and digital financial innovations. This study employs a qualitative method with a normative approach and literature analysis of classical sources as well as contemporary studies. The findings indicate that the definitions and classifications of riba in fiqh muamalah, such as riba al-fadl and riba al-nasi’ah, are grounded in philosophical principles that emphasize distributive justice and the protection of vulnerable parties. However, in the context of the modern economy, challenges arise in the form of interest-based banking systems, credit mechanisms, and financial instruments that often occupy a grey area between prohibited riba and economic necessity. Therefore, a contextual reinterpretation through contemporary ijtihad is required to ensure that Islamic principles remain relevant without neglecting the demands of global economic development. This article contributes to the discourse of Islamic commercial jurisprudence by offering an integrative analytical framework that bridges normative texts and modern empirical realities.